Social media as a complementary learning tool for teaching and learning: The case of youtube - Moghavvemi, Sedigheh; Sulaiman, Ainin; Jaafar, Noor Ismawati; Kasem, Nafisa (Elsevier, 2018)
Taking into account the importance of using video and visual objects for teaching, some universities utilize YouTube as a complementary teaching tool. This work analyses students’ perspectives on the usage of YouTube for learning, their corresponding usage patterns, and associated factors prompting them to use YouTube. We interviewed 30 students, and went on to develop a scale for academic learning as a determinant of YouTube usage, which was then validated amongst the students. Data were collected from a total of 321 students in the Faculty of Business and Accountancy, University of Malaya to test the developed construct. The results confirmed that entertainment, seeking information, and academic learning are some of the main motivations for using YouTube. We regard YouTube as an effective tool that can enhance the learning experience if the video is indeed relevant to the subject at hand. It is recommended that instructors integrate YouTube into their respective courses to benefit from its inherent advantages in the context of learning/teaching.